Evaluation of a targeted, theory-informed implementation intervention designed to increase uptake of emergency management recommendations regarding adult patients with mild traumatic brain injury : results of the NET cluster randomised trial - Gruen, Russell Lindsay (2019)
Background : Evidence-based guidelines for management of mild traumatic brain injury (mTBI) in the emergency department (ED) are now widely available; however, clinical practice remains inconsistent with these guidelines. A targeted, theory-informed implementation intervention (Neurotrauma Evidence Translation (NET) intervention) was designed to increase the uptake of three clinical practice recommendations regarding the management of patients who present to Australian EDs with mild head injuries. The intervention involved local stakeholder meetings, identification and training of nursing and medical local opinion leaders, train-the-trainer workshops and standardised education materials and interactive workshops delivered by the opinion leaders to others within their EDs during a 3 month period. This paper reports on the effects of this intervention. Methods : EDs (clusters) were allocated to receive either access to a clinical practice guideline (control) or the implementation intervention, using minimisation, a method that allocates clusters to groups using an algorithm to minimise differences in predefined factors between the groups. We measured clinical practice outcomes at the patient level using chart audit. The primary outcome was appropriate screening for post-traumatic amnesia (PTA) using a validated tool until a perfect score was achieved (indicating absence of acute cognitive impairment) before the patient was discharged home. Secondary outcomes included appropriate CT scanning and the provision of written patient information upon discharge. Patient health outcomes (anxiety, primary outcome: Hospital Anxiety and Depression Scale) were also assessed using follow-up telephone interviews. Outcomes were assessed by independent auditors and interviewers, blinded to group allocation. Results : Fourteen EDs were allocated to the intervention and 17 to the control condition; 1943 patients were includedin the chart audit. At 2 months follow-up, patients attending intervention EDs (n= 893) compared with control EDs (n= 1050) were more likely to have been appropriately assessed for PTA (adjusted odds ratio (OR) 20.1, 95%CI 6.8 to 59.3; adjusted absolute risk difference (ARD) 14%, 95%CI 8 to 19). The odds of compliance with recommendations for CT scanning and provision of written patient discharge information were small (OR 1.2, 95%CI 0.8 to 1.6; ARD 3.2, 95%CI−3.7 to 10 and OR 1.2, 95%CI 0.8 to 1.8; ARD 3.1, 95%CI−3.0 to 9.3 respectively). A total of 343 patients at ten interventions and 14 control sites participated in follow-up interviews at 4.3 to 10.7 months post-ED presentation. The intervention had a small effect on anxiety levels (adjusted mean difference−0.52, 95%CI−1.34 to 0.30; scale 0–21, with higher scores indicating greater anxiety). Conclusions : Our intervention was effective in improving the uptake of the PTA recommendation; however, it did not appreciably increase the uptake of the other two practice recommendations. Improved screening for PTA may be clinically important as it leads to appropriate periods of observation prior to safe discharge. The estimated intervention effect on anxiety was of limited clinical significance. We were not able to compare characteristics of EDs who declined trial participation with those of participating sites, which may limit the generalizability of the results.